Characterization of the depsidone gene cluster reveals etherification, decarboxylation and multiple halogenations as tailoring steps in depsidone assembly - Jiafan Yang; Zhenbin Zhou; Yingying Chen; Yongxiang Song; Jianhua Ju (Elsevier, 2023)
Depsides and depsidones have attracted attention for biosynthetic studies due to their broad biological activities and structural diversity. Previous structure‒activity relationships indicated that triple halogenated depsidones display the best anti-pathogenic activity. However, the gene cluster and the tailoring steps responsible for halogenated depsidone nornidulin (3) remain enigmatic. In this study, we disclosed the complete biosynthetic pathway of the halogenated depsidone through in vivo gene disruption, heterologous expression and in vitro biochemical experiments. We demonstrated an unusual depside skeleton biosynthesis process mediated by both highly-reducing polyketide synthase and non-reducing polyketide synthase, which is distinct from the common depside skeleton biosynthesis. This skeleton was subsequently modified by two in-cluster enzymes DepG and DepF for the ether bond formation and decarboxylation, respectively. In addition, the decarboxylase DepF exhibited substrate promiscuity for different scaffold substrates. Finally, and interestingly, we discovered a halogenase encoded remotely from the biosynthetic gene cluster, which catalyzes triple-halogenation to produce the active end product nornidulin (3). These discoveries provide new insights for further understanding the biosynthesis of depsidones and their derivatives.